A rare case of recurrent hypertrophic pyloric stenosis - Clint D. Cappiello; Eric Strauch (Elsevier, 2014)
Hypertrophic pyloric stenosis (HPS) is perhaps the most commonly encountered gastrointestinal disease process in the pediatric surgical patient. While the etiology remains unclear, progression of the disease is well described and uniformly results in non-bilious emesis, weight loss and metabolic derangement. Current management of HPS is the Ramstedt procedure; complications are minimal and the procedure is curative. True recurrence of HPS is rare, and usually mistaken for an incomplete myotomy. We present here a case of recurrent pyloric stenosis after complete myotomy.